POLISH-UKRAINIAN RELATIONS IN 2014 – 2022: MILITARY DIPLOMATIC VECTOR OF COOPERATION - KRASIVSKYY, Orest (EAST EUROPEAN HISTORICAL BULLETIN, 2025)
The purpose of the research is to clarify the Polish-Ukrainian relations formation in the context of the foreign policy concepts of the Republic of Poland and the conditions of the process of activating Ukraine’s European integration, Russia’s war against Ukraine since 2014. The methodology of the research is based on the principles of historicism, scientific objectivity in assessments. There have been used the problem chronological, logical, deductive and inductive methods. The Scientific Novelty. There have been outlined the main principles of the Polish foreign policy in the article, taking into account the geopolitical concepts developed in previous decades, in particular the modernized ideas of Giedroyc, the “Jagiellonian” and “Piast” doctrines. The role of Ukraine in these geopolitical regional concepts has been analyzed. The system of the military political interaction between Ukraine and Poland within the framework of the trilateral regional alliance “The Lublin Triangle”, the joint military formation “LitPolUkrBrig”. There have been considered various levels of political and military cooperation between Ukraine and Poland in the context of countering the armed aggression of the Russian Federation after 2014, military and technical assistance of the Republic of Poland from 2014 to 2023. The Conclusions. Intensification of the Polish-Ukrainian relations took place at the turn of 2013 – 2014 in the context of Euromaidan, the Revolution of Dignity, and the Russian armed aggression in 2014. During the period of 2014 – 2022, Poland provided significant support to Ukraine at the bilateral and international levels. The establishment of good-neighbourly relations and military political assistance to Ukraine was implemented by Poland through the prism of implementing the “Intermarium” concept, and later the “Three Seas Initiative”, which reflect a broader geopolitical doctrine that takes into account the historical past and the desire to become one of the dominant powers in Central and Eastern Europe. Since 2015, after the victory of Andrzej Duda in the presidential elections, the parliamentary elections of Jarosław Kaczyński, and even more intensively since 2017, Poland has been abandoning a unilateral policy oriented towards the West. Instead, Poland is implementing a policy of integration of EU member states located between the Adriatic, Baltic, and Black Seas. That is, the interwar project “Intermarium” in the context of the new European geopolitical configuration is transforming into the “Three Seas Initiative” – “Three Seas”. It is worth noting that the security sphere remained a priority in the Polish policy, as evidenced by a number of initiatives, including the creation of the Lithuanian-Polish-Ukrainian Brigade (“LitPolUkrBrig”); joint military training, “the Lublin Triangle” project. A set of measures that contribute to strengthening military cooperation between states, mastering advanced technologies and training standards of the Armed Forces of Ukraine is extremely important in the context of the full-scale invasion of Ukraine by the Russian Federation in February of 2022 and the threat of further aggression in the region. Therefore, Poland increased its assistance to Ukraine in the military, financial, and humanitarian spheres significantly. From mid-2022 to early 2023, it became the second country after the United States in terms of the scale of military assistance to Ukraine. Key words: Ukraine-Poland, Polish-Ukrainian relations, Jerzy Giedroyc’s postulates, “Jagiellonian” and “Piast” doctrines, the concept of “Intermarium”, “Lublin Triangle”, Lithuanian-Polish-Ukrainian Brigade ("LitPolUkrBrig"), security issues, countering Russian aggression, cooperation in the field of defense, military and technical and humanitarian assistance to Poland.